A MODEL TO STUDY THE INFLUENCE OF REQUIREMENT ENGINEERING TECHNIQUES ON CRITICAL CHALLENGES IN SMALL AND MEDIUM SOFTWARE ENTERPRISE - BESROUR, SOUHAIB (2018)
Requirement engineering (RE) is the process of defining, analyzing, specifying and validating software requirement. Numerous recent studies reported that requirement errors have a negative effect on software project, that leads to waste in both project time and budget. Thus, various RE techniques have been proposed to reduce the effect of RE challenges such as ambiguous requirement, complex requirement and poor requirement understanding, etc.